Harnessing Magnetic Properties for Precision Thermal Control of Vortex Domain Walls in Constricted Nanowires - Mohammed Al Bahri; Salim Al-Kamiyani (Nanomaterials)
This study investigates the thermal pinning and depinning behaviors of vortex domain walls (VWs) in constricted magnetic nanowires, focusing on the influence of intrinsic magnetic properties on VW stability under thermal stress. Using micromagnetic simulations, we analyze the roles of saturation magnetization (Ms), uniaxial magnetic anisotropy (Ku), and nanowire geometry in determining VW thermal stability. The modeled nanowire has dimensions of 200 nm (width), 30 nm (thickness), and a 50 nm constriction length, chosen based on the dependence of VW formation on nanowire geometry. Our results show that increasing Ms and Ku enhances VW pinning, while thermal fluctuations at higher temperatures promote VW depinning. We demonstrate that temperature and magnetic parameters significantly impact VW structural stability, offering insights for designing high-reliability nanowire-based memory devices. These findings contribute to optimizing nanowire designs for thermally stable, energy-efficient spintronic memory systems.